The Effectiveness of the Process Oriented Guided Inquiry Learning (POGIL) Model in Educational Psychology Learning - Sri Haryati (International Journal of Pedagogy and Teacher Education, 2018)
Theoretically, this research contributes to: (1) the development of educational psychology theory, and (2) the development of research-based learning theory; the research results are especially relevant to methods such as authentic learning, problem-based learning, cooperative learning, inquiry learning, process oriented guided inquiry learning (POGIL) and contextual teaching and learning, which are currently increasingly popular. Practically, this research can be used as a teaching material for lecturers and students in lectures, and may be particularly beneficial as a comparative or supplemental book to enrich the educational psychology materials used in a new course of Faculty of Education and Teachers’ Training at Tidar University. The objectives of this study were: (1) to propose appropriate learning materials for the subject of educational psychology using research-based learning models, and (2) to test the effectiveness of research-based learning models, especially POGIL. The research was conducted among the second semester students in English Education Study Program. The research method used was Research and Development, which consisted of three steps, namely preparation, development, and reporting of results. The data analysis technique used was one group pre-test post-test design. This research succeeded in developing teaching materials for educational psychology using a research-based learning model and indicates that POGIL can improve students’ learning outcomes. The research results show that: (1) there is a significant difference between learning outcomes before and after learning using the POGIL model, as proven by the increase in the mean score from 58 to 91, and (2) there is no significant difference between the three sample groups using POGIL model in their learning, as proven by t-count being smaller than t-table, and the average post-test score of both groups 1 and 2 being 90, and the average post-test score of group 3 being 93.